Meningkatkan Karakter Mandiri Melalui Video Pembelajaran sebagai Media Pembelajaran Jarak Jauh - Suwanto Suwanto (Direktorat Guru Pendidikan Dasar, Kemendikbudristek R.I., 2022)
The background of the problem in this research is that learning is limited to the new normal in which some students study at school and at home. Even so, learning must still prioritize character education for students. One of the learning strategies at home is to use learning videos uploaded on YouTube. The objectives of this research are to describe (1) the learning video process is able to improve independent character in English greeting card material, (2) the results of the teaching and learning process using learning videos that can improve independent character in English greeting card material, and (3) changes in behavior/attitudes in students after using learning videos. The research approach used is Research and Development. The development stage used the Alessi & Trollip model including planning, design, and development. The findings are as follows; The gain index was obtained at 0.43 medium category, which means that learning videos are effectively used for the teaching and learning process during the pandemic, learning completeness from 12.5% to 93.75% has increased by 81.25%, the independent attitude of students has increased significantly, previously by 50% to 62.50% and an increase of 12.50%, the results of the material and media expert instrument are 4. This shows that learning videos are suitable for use for junior high school.